Therapeutic plasma exchange: Review of current indications - Fernández-Zarzoso, Miguel; Gómez-Seguí, Inés; de la Rubia, Javier (Transfusion and apheresis science, 2019)
Therapeutic plasma exchange (TPE) is the extracorporeal technique performed in an apheresis device were patient’s plasma is separated from whole blood and removed, while the cellular blood components are returned to the patient together with a replacement fluid. By the extracorporeal removal of pathological substances and the replacement of deficient plasma components, it constitutes an important tool for the management of several disorders and it is a well-known and established treatment for numerous diseases. Additionally, overall available data confirm the safety and efficacy of TPE. Nevertheless, the quality of the evidence supporting the utility and efficacy of the procedure is diverse. This review attempts to compile the current indications of TPE in different disorders according to an extensive and updated literature review, with special focus on its present role and its validity in the twenty-first century medicine.